Analisis Tindak Tutur Ekspresif dalam Film Home Sweet Loan Karya Almira Bastari Kajian Pragmatik - Ibrahim, Tiara; Rahmi, Elvi; Indryani, Dian (LP4MK STKIP PGRI Lubuklinggau, 2025)
This study examines expressive speech acts in Almira Bastari's film